2020
DOI: 10.3390/membranes10080180
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Evaluation of WWTP Renovation Based on Applying Ultrafiltration Membrane

Abstract: Nowadays, the standards of discharging are gradually becoming stricter, since much attention has been paid to the protection of natural water resources around the world. Therefore, it is urgent to upgrade the existing wastewater treatment plant (WWTP), to improve the effluent quality, and reduce the discharged pollutants to the natural environment. In this paper, taking the “Liaocheng UESH (UE Envirotech) WWTP in Shandong province of China” as an example, the existing problems and the detailed measures for a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The MoS 2 suspensions were adjusted to pH 6 by adding diluted hydrochloric acid and sodium hydroxide solution. A pH of 6 is within the typical pH range of surface water, and thus our findings can provide useful insights into the alteration of MoS 2 nanosheets released in environmental systems . To ensure a consistent ionic strength (IS) during the dissolution tests and understand its effects on the dissolution of MoS 2 , either 1 or 10 mM NaCl was used, and the MoS 2 suspensions were mildly stirred.…”
Section: Methodsmentioning
confidence: 93%
“…The MoS 2 suspensions were adjusted to pH 6 by adding diluted hydrochloric acid and sodium hydroxide solution. A pH of 6 is within the typical pH range of surface water, and thus our findings can provide useful insights into the alteration of MoS 2 nanosheets released in environmental systems . To ensure a consistent ionic strength (IS) during the dissolution tests and understand its effects on the dissolution of MoS 2 , either 1 or 10 mM NaCl was used, and the MoS 2 suspensions were mildly stirred.…”
Section: Methodsmentioning
confidence: 93%
“…It involved a capital expenditure of $210,000, and it was found that the operating cost to maintain the unit was low, which is not expensive to set up a unit in the region where the study was conducted. Recently a study on process upgradation of a wastewater treatment plant was done by Bai et al [29]. It was found that the renovation of the plant with a UF membrane technology is feasible, and the investment amounts up to CNY 25.626 million for a production capacity of 1250 m 3 /h of wastewater.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These have tended to concentrate on particular physical or chemical facets of the treatment technology, employing cost analysis for optimisation purposes. Recent examples of such topics (Table 1) include pre-treatment using powdered activated carbon (PAC) (Campinas et al, 2021) or coagulant (Arhin et al, 2019), maintenance optimisation with reference backwashing (Bai et al, 2020) or chemical cleaning (Yoo et al, 2018), module design (Lee et al, 2020), and membrane material -and in particular the cost comparison of ceramic and polymeric membranes (Hurvitz et al, 2018;Park et al, 2015;Pellegrino, 2012, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (Hurvitz et al, 2018;Yoo et al, 2018;Zheng et al, 2011) have been limited to operating expenditure (OPEX), based largely on a consideration of energy and consumables. Some of the studies which have encompassed capital costs have been based on a single flow capacity (Bai et al, 2020;Park et al, 2014;Pellegrino, 2012, 2013). Correlations reported in these studies have been generated from either outputs from trials conducted at bench or pilot scale (Guerra and Pellegrino, 2012) or a single full-scale reference installation (Bai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%